Cysteine-rich 61 mediates inflammation by the NF-κB/cyclooxygenase-2 pathway in RF/6A cells - Po-Ting Yeh; Jian-Jang You; Chang-Hao Yang (Taiwan Journal of Ophthalmology)
PURPOSE: Cysteine-rich 61 (Cyr61) may enhance angiogenesis and inflammation in diabetic retinopathy (DR). Cyclooxygenase-2 (COX-2) is an immediate-early gene product of inflammation and it also plays an important role in developing DR. We aim to investigate the effects of Cyr61 on COX-2 expression in chorioretinal vascular endothelial (RF/6A) cells and to study the possible signal transduction pathway and the transcriptional mechanisms. MATERIALS AND METHODS: The effects of Cyr61 on COX-2 expression were evaluated via determining the mRNA, protein, and prostaglandin (PG) E2 levels of RF/6A cells. To examine the pathway in this process, RF/6A cells were pretreated with integrin ανβ3-blocking antibodies, a FAK inhibitor (PF573228), a PI3K inhibitor (LY294002), and an Akt inhibitor (A6730), respectively. Electrophoretic mobility shift assays (EMSAs) and luciferase reporter assays were applied to assess if NF-κB was involved in this response. RESULTS: Cyr61 stimulated the expression of COX-2 at the mRNA, protein, and PGE2 levels in a dose-dependent and time-dependent manner. Both COX-2 and PGE2 levels were attenuated during the response to Cyr61 stimulation by pretreatment with integrin ανβ3-blocking antibodies, PF573228, LY294002, and A6730 respectively. EMSA revealed that all of the aforementioned inhibitors suppressed NF-κB activation. Luciferase reporter assays further indicated that the mutation of the NF-κB-binding element in the COX-2 gene promoter reduced its gene expression. CONCLUSIONS: Induction of COX-2 by Cyr61 is mediated through the activation of the integrin ανβ3, FAK, PI3K/Akt, and NF-κB pathways in RF/6A cells.